2012
DOI: 10.36531/ijds.2012.68137
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Influence on the Chemical Content and Some Rheologicaly Properties for Natural Asphalt to Abu Aljeer _ Alanbar

Abstract: Heating of natural asphalt at high temperatures for a long time lead to oxidation of the asphalt , which starting on the surface while with continuous mixing and heating leads to oxidation to all the asphalt molecules and the texture of oxidized asphalt becomes a solid , glossy, dark black of color. The rheological properties before and after oxidation were studied , the results showed that increase of oxidation time , Lead to reduce the degree of penetration(increased stiffness) and an increment in the soften… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In its natural state, NA is not suitable for pavement applications. To address this, heat treatments over varying intervals (5,10,15,20,25 hrs.) are administered to NA, adjusting its properties to meet the desired performance levels of HMA.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In its natural state, NA is not suitable for pavement applications. To address this, heat treatments over varying intervals (5,10,15,20,25 hrs.) are administered to NA, adjusting its properties to meet the desired performance levels of HMA.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Test results from the Abdul-Jaleel and Najres [25] study indicated that the thermal oxidation of NA from Abu Aljeer at high temperatures under atmospheric conditions improved its chemical and physical properties, increased the ratio of asphaltene and aromatic parts, and decreased the ratio of saturated and resinous parts. The study also revealed a relationship among the chemical content of asphalt, oxidation processes, and the stability of the colloidal state.…”
Section: Introductionmentioning
confidence: 99%